A multiscale study of the filler-size and temperature dependence of the thermal conductivity of graphene-polymer nanocomposites. (30th April 2021) - Wang, Jie; Li, Chao; Li, Jackie; Weng, George J.; Su, Yu
Abstract: The size of graphene nanofillers and the ambient temperature are two important factors for the effective thermal conductivity of graphene nanocomposites. However, these two issues together are seldom considered in theoretical evaluation of the overall thermal property. By introducing the size-dependent thermal transport mechanisms (quasi-ballistic heat flow and diffusive heat transport) to the Landauer-like theory, we established a new method to calculate the in-plane size and temperature dependence of the thermal conductivity of graphene nanofillers from the nanoscale perspective, which is crucial for the overall thermal conductivity of the nanocomposites. The validity of this approach was confirmed by nonequilibrium molecular dynamics simulation. Then the filler-size- and temperature-dependent thermal conductivity of graphene nanocomposites was calculated via an effective-medium approximation based on Maxwell's far-field matching at a microscopic level. We highlight this multiscale approach with its implementation in the estimation of the overall thermal conductivity of graphene-polymer nanocomposites. The results are shown to be in close agreement with the experimental observations over the average filler size from 200 to 1000 nm and over the temperature from 300 to 360 K, respectively. This study revealed the significant effects of the graphene-filler size and the ambient temperature on the thermal conductivity of the nanocomposites. Graphical abstract: Image 1